Intrathecal cdk5 inhibitor, roscovitine, attenuates morphine antinociceptive tolerance in rats - WANG Cheng-haung; LEE Tsung-hsing; TSAI Yi-jung; LIU Jong-kang; CHEN Yann-jang; YANG Lin-cheng; LU Cheng-yuan (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of cyclin-dependent kinase 5 (Cdk5) inhibitor roscovitine on the morphine antinociceptive tolerance development in rats. METHODS: Tail-flick test as pain threshold measurement and intrathecal injection techniques were used. RESULTS: Intrathecal roscovitine infusion alone produced an antinociceptive effect. Tolerance was induced by continuous intrathecal infusion of morphine 5 microg/h for 5 d. Co-administration of intrathecal roscovitine 1 microg/h for 5 d enhanced the morphine antinociceptive effect in tolerant rats. It also caused a shift in the morphine antinociceptive dose-response curve to the left when co-administered with morphine during tolerance induction, and caused a 67 % reduction in the increase in the ED50 of morphine (dose producing 50 % of the maximum response). CONCLUSION: Cdk5 modulation is involved in the antinociceptive tolerance of morphine. Intrathecal roscovitine administration could attenuate this tolerance development.